2019
DOI: 10.15171/hpp.2019.35
|View full text |Cite
|
Sign up to set email alerts
|

The global prevalence of maternal near miss: a systematic review and meta-analysis

Abstract: Background: Improving the maternal health is one of the world’s most challenging problems. Despite significant movements over the past decades, maternal health has been still considered as a central goal for sustainable development. Maternal near miss (MNM) cases experience long-term physical and psychological effects. To present a clear portrait of the current situation, we performed a systematic review and meta-analysis with the purpose to assess the worldwide prevalence of MNM. Methods: We conducted a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 56 publications
(14 reference statements)
1
44
0
1
Order By: Relevance
“…Mothers who due to childbirth morbidities have gone close to death, but have had a narrow escape, experience near-miss conditions [1,2] and experience long-term negative psychological and emotional effects [3,4,5,6,7], and along with organ dysfunction and physical problems, they experience anxiety, isolation, depression, and trauma childbirth [8,9]. Other family members and the infant will not be immune to these negative effects, either [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Mothers who due to childbirth morbidities have gone close to death, but have had a narrow escape, experience near-miss conditions [1,2] and experience long-term negative psychological and emotional effects [3,4,5,6,7], and along with organ dysfunction and physical problems, they experience anxiety, isolation, depression, and trauma childbirth [8,9]. Other family members and the infant will not be immune to these negative effects, either [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…A global systematic review -in a large multicountry study revealed that based on WHO approach, the prevalence of MNM cases in health facilities was 18.67 per 1000 live births [3]. Per each maternal mortality case, an estimated of 20 mothers survive but they go on to experience the consequences of related morbidities, with long-term effects on their mental and physical health [4,5]; however, no precise information is available about their lives after being saved from death.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the World Health Organization (WHO) organized an expert group to review and revise the concept of maternal near-miss (MNM) in 2009, which clarify the diagnostic criteria from three aspects: clinical standards, laboratory tests, and disease management standards. MNM means that pregnant women who are on the verge of death within 42 days of pregnancy, childbirth, and postpartum are successfully rescued or continue to survive due to accidental factors [5]. MNM's condition changes are bidirectional [6].…”
Section: Introductionmentioning
confidence: 99%